Misi dan rekonsiliasi: Merevitalisasi fungsi gereja di tengah konflik sosial - Labobar, Kresbinol (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2024)
This article aims to revitalize the church's function as a bearer of the mission of reconciliation amid social conflict, especially in Indonesia. Since the era of reform, which was considered to bring fresh air of change to the nation's life, horizontal conflicts have escalated. The church's presence, which cannot be separated from God's mission, is more often associated with the mission of evangelism. Through descriptive analysis of various literature, it was found that the mission built on the paradigm of the Triune God and the incarnation of Christ resulted in a reconciliatory mission. Therefore, the concept of a